2000
DOI: 10.4049/jimmunol.164.4.1898
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of CTL Epitope Processing by Single Amino Acid Substitution Flanking the C-Terminal Proteasome Cleavage Site

Abstract: CTL directed against the Moloney murine leukemia virus (MuLV) epitope SSWDFITV recognize Moloney MuLV-induced tumor cells, but do not recognize cells transformed by the closely related Friend MuLV. The potential Friend MuLV epitope has strong sequence homology with Moloney MuLV and only differs in one amino acid within the CTL epitope and one amino acid just outside the epitope. We now show that failure to recognize Friend MuLV-transformed tumor cells is based on a defect in proteasome-mediated processing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 50 publications
3
74
0
Order By: Relevance
“…The cleavage occurs between the P1 and the P1 0 position (Berger and Schechter 1970). It has been suggested that the P1 position is the most important position determining cleavage (Altuvia and Margalit 2000;Cascio et al 2001), although the flanking region may also be important (Ossendorp et al 1996;Beekman et al 2000;Mo et al 2000). One way of analyzing such data is to calculate the information content at the cleavage site and in the region flanking the cleavage site.…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage occurs between the P1 and the P1 0 position (Berger and Schechter 1970). It has been suggested that the P1 position is the most important position determining cleavage (Altuvia and Margalit 2000;Cascio et al 2001), although the flanking region may also be important (Ossendorp et al 1996;Beekman et al 2000;Mo et al 2000). One way of analyzing such data is to calculate the information content at the cleavage site and in the region flanking the cleavage site.…”
Section: Resultsmentioning
confidence: 99%
“…20S proteasomes were purified from a Epstein-Barr virus (immuno proteasome) and a HeLa cell line (constitutive proteasome) as described (24). Low molecular mass polypeptide 2 (LMP2) and LMP7 contents were confirmed by 2D immunoblotting (data not shown).…”
Section: Transporter Associated With Antigen Presentation (Tap) Transmentioning
confidence: 99%
“…SVM-Models trained using sparse sequence representation were selected. (A) Predictive performance (R p ) of SVM-models with regard to the fragment size used for training (1)(2)(3)(4)(5)(6)(7)(8)(9). Only the largest R p value achieved by a specific model (indicated in the abscissa) at each fragment size is represented.…”
Section: Resultsmentioning
confidence: 99%